Tetranuclear manganese(II) complexes of hydrazone and carbohydrazone ligands: Synthesis, crystal structures, magnetic properties, Hirshfeld surface analysis and DFT calculations - Abedi, Marjan; Yesilel, Okan Zafer; Mahmoudi, Ghodrat; Bauza, Antonio; Lofland, Samuel E.; Yerli, Yusuf; Kaminsky, Werner; Garczarek, Piotr; Zareba, Jan K.; Ienco, Andrea; Frontera, Antonio; Gargari, Masoumeh Servati (ELSEVIER SCIENCE SA, 2016)
The complexes [Mn-4(L1)(4)(N-3)(4)] (1), [Mn-4(L2)(4)(mu-N-3)(2)(N-3)(2)(OCH3)(2)] (2) and [Mn-4(mu-L3)(4)(NCS)(4)]center dot 6CH(3)OH (3) [L1 = N-1-(pyridin-2-yl)ethylidenepicolinohydrazonate, L2 = N-phenyl(pyridin-2-yl)methylenepicolino hydrazonate, and L3 = ((phenyl(pyridin-2-yl) methylene)hydrazinyl)((Z)-2-(phenyl(pyridin-2-yl) methylene) hydrazinyl) methanolate] have been synthesized, and their structures characterized. The structures of 1 and 3 can be described as tetranuclear and are formed from four Mn(II) ions bridged by four ligands. Complex 2 exhibits a centrosymmetric tetranuclear structure with two types of Mn(II) centers with double end-on (EO) azido bridges. All the complexes have similar magnetic behavior and exhibit weak intramolecular antiferromagnetic coupling, which is consistent with the oxygen-bridged square structures with large Mn-O-Mn bridge angles. Theoretically obtained J values of -1.7 cm(-1) (for 1), -0.7 cm(-1) (for 2) and -3.3 cm(-1) (for 3) corroborate well the experimental results. Moreover, a Hirshfeld surface (HS) analysis was employed to gain additional insight into interactions responsible for packing of complexes 1-3 (with d(norm) and shape-index functions). Quantitative examination of 2D fingerprint plots revealed, amongst others, the dominating participation of H center dot center dot center dot H and H center dot center dot center dot C interactions in the molecular packing. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Hydrazone ligands; Tetranuclear complex; Manganese(II) complexes; Magnetism; END-ON AZIDO; EXCHANGE COUPLING-CONSTANTS; INTERMOLECULAR INTERACTIONS; POLYNUCLEAR COMPLEXES; TRANSITION; GRIDS; POLYMERS; CLUSTERS; TECTONS; FAMILY; Chemistry